2021
DOI: 10.1016/j.cell.2021.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Xist nucleates local protein gradients to propagate silencing across the X chromosome

Abstract: Since publication of the original article, we have become aware of three errors in our paper that we are now correcting. (1) The author list omitted Joanna W. Jachowicz and Mackenzie Strehle. They contributed the initial observation that the intrinsically disordered region of SPEN is critical for silencing some genes on the X chromosome, and we are now including them as authors. The author list, affiliations, and author contributions have been updated online, and all co-authors have approved the changes. (2) W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 0 publications
2
20
0
Order By: Relevance
“…Indeed, 75% of human long non-coding transcripts contain at least a partial retroviral insertion and thus repetitive sequences [24] that may naturally act as molecular crowders to rewire cellular compartmentalization in response to environmental cues. Such a model may solve the conservation and concentration paradox by explaining how stochastic events such as the aberrant expression of lncRNAs can give rise to conserved functions even at low concentrations [32] . Supporting this hypothesis, it was recently demonstrated that two copies of Xist, a lncRNA necessary for X inactivation in placental mammals and implicated in the development of haematological cancers in Mus musculus [33], are sufficient to enucleate 50 macromolecular foci, containing the critical silencing protein SPEN [32].…”
Section: Cellular Compartmentalization: Order Emerging From Chaosmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, 75% of human long non-coding transcripts contain at least a partial retroviral insertion and thus repetitive sequences [24] that may naturally act as molecular crowders to rewire cellular compartmentalization in response to environmental cues. Such a model may solve the conservation and concentration paradox by explaining how stochastic events such as the aberrant expression of lncRNAs can give rise to conserved functions even at low concentrations [32] . Supporting this hypothesis, it was recently demonstrated that two copies of Xist, a lncRNA necessary for X inactivation in placental mammals and implicated in the development of haematological cancers in Mus musculus [33], are sufficient to enucleate 50 macromolecular foci, containing the critical silencing protein SPEN [32].…”
Section: Cellular Compartmentalization: Order Emerging From Chaosmentioning
confidence: 99%
“…Such a model may solve the conservation and concentration paradox by explaining how stochastic events such as the aberrant expression of lncRNAs can give rise to conserved functions even at low concentrations [32] . Supporting this hypothesis, it was recently demonstrated that two copies of Xist, a lncRNA necessary for X inactivation in placental mammals and implicated in the development of haematological cancers in Mus musculus [33], are sufficient to enucleate 50 macromolecular foci, containing the critical silencing protein SPEN [32]. Overall, these observations suggest that a re-evaluation of the concepts of specificity and stoichiometry in RNA-protein interactions, may be necessary.…”
Section: Cellular Compartmentalization: Order Emerging From Chaosmentioning
confidence: 99%
“…Even in low copy numbers, lncRNAs can initiate the formation of nuclear compartments by interacting with RBPs to regulate transcription [15]. LncRNAs are reported to form scaffolds with RBPs and other mediator proteins that regulate the process of transcription and chromatin remodeling [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA often work by recruiting epigenetic regulators to locally concentrate them at target chromatin (Markaki et al , 2021). Our RNA-affinity purification relies on protein- RUS interactions formed under physiological conditions in intact cells and purifying complexes under native conditions.…”
Section: Discussionmentioning
confidence: 99%